Study on phased strategies for sustainable aviation fuel (SAF) industrialization based on a tripartite evolutionary game - Zhou, Lianbin; Wang, Xi; Zhang, Peiwen; Jiang, Weiwei (Frontiers in Environmental Science, 2026)
Against the “high-carbon lock-in” dilemma in sustainable aviation fuel (SAF) industrialization, which is caused by high costs, insufficient supply, and a lack of policy coordination, this study constructs a tripartite evolutionary game model involving governments, airlines, and fuel producers to examine industrialization across initial, developmental, and mature stages. We establish dynamic replication equations, solve Jacobian matrices, and conduct numerical simulations to reveal evolutionary paths and equilibrium conditions of strategic interactions among the three parties at different stages. The results show that a high-intensity policy mix of over 60% government subsidies for airlines SAF purchase premiums plus a high carbon tax is required initially to break the deadlock; in the development stage, airlines need to cover at least 33.3% of fuel producers R&D costs and offer no less than 15% profit share, while carbon tax intensity should increase by more than 60%. The results show that in the initial stage, a high-intensity policy combination of “government subsidies covering more than 60% of airlines’ SAF purchase premium + high carbon tax” must be implemented to break the “high-carbon lock-in” deadlock during the introduction period of industrialization. In the development stage, to address the bottleneck of “weak supply-demand coordination”, airlines need to bear no less than 33.3% of fuel producers’ R&D costs through investment and provide a profit share of no less than 15%. Moreover, the intensity of the carbon tax should be increased to more than 1.6 times the original level. In the mature stage, the carbon quota price for airlines should be set such that the selling price is at least 0.75 times the purchase cost. Under this premise, the SAF will gradually gain cost competitiveness and economies of scale. This study further proposes building a dual-drive mechanism integrating green finance, offtake agreements and industrial chain equity investment, and suggests government shift from “dominant supervision” to “service support”, and solve the problem of “lack of market mechanisms” by improving the carbon market and emission evaluation system, ultimately promoting the SAF to achieve a fundamental transformation from “policy dependence” to “market autonomy”.